The Influence of Peer Group Education on Menstrual Hygiene on Knowledge of Pruritusvulvae Prevention in Adolescent Girls at SMP Muhammadiyah 4 Medan - Triana, Heni; Lilis Pujiati; Suherni, Suherni (International Journal of Public Health Excellence (IJPHE), 2024)
The importance of education and health reproduction at SMP Muhammadiiyah 4 Medan is often neglected. Whereas prevalence problems in health reproduction in adolescents at SMP Muhammadiiyah 4 Medan are still high, including anemia, vaginal discharge, dysmenorrhea, syndrome premenstrual, and hygiene problems. Difficulties can have an impact, like school absenteeism, wasting, and infertility. Peer education seen as capable of overcoming problemsThis is because teenagers at SMP Muhammadiiyah 4 Medan more often interact with friends and peers than with family, teachers, or officers. Purpose of activity: This is to increase knowledge, attitudes, and skills of participants about education, peers, and health reproduction among teenagers. Health education for teenagers, peer education training, and mentoring activities are potential extracurriculars that help the realization of healthy madrasas. A number of activities are performed. Activity This is followed by three to ten students who want to become peer educators. Results of activities evaluated use pre-test and post-test questionnaires, as well as practice education, health, and counseling. Result of activity: This is an enhancement knowledge participant about health reproduction among teenagers of 8.28 and peer education of 5.17 after the follow-up activity. Participants are also capable of recognizing health problems, common reproduction that appears in adolescence, and manner prevention.